(untitled) (Journal of Green Business School, 2025)
While analyzing major determinants of the financial effectiveness of AB Ltd. it is clear that ROA & ROE are yet to be developed through controlling the spread cost of deposit, cost of borrowing, credit deposit ratio, stuck-up advances, increasing recovery, diversion of funds, working funds, etc. Practically more prudent project appraisals, credit analysis, effective monitoring and supervision of ethical practices are the major steps to be adopted by bank management to face the local and global challenges in the fund management practices of our commercial banks. J. of Green Business. Sch. Vol 6(1), Jan-Dec, 2023; pp 53-68